THEORETICAL BASES OF ECONOMIC MEASUREMENTS OF VALUE IN THE CONDITIONS OF GLOBAL TECHNOLOGICAL SHIFTS AND CRISES. NEWEST METHODOLOGICAL BASIS (PART 1) - O. E. Medvedeva; A. I. Artemenkov (Вестник университета, 2020)
Problems of measuring scientific and technological progress (STP) in the transition to the sixth technological mode have been considered. Now STP is measured mainly by natural indicators. Forecasting requires a valuation of capital, taking into account fluctuations in the interest rate at the macro level;assessment of public production efficiency and new technologies. Unified applied methodology for such assessments has not yet been formulated. For these purposes, the methodology of the theory of economic measurements, which is also in its infancy, and its latest concepts, can serve. In relation to STP, the object of assessment can be the value of capital and its depreciation in the final phase of the transition period, the effectiveness of STP and money itself, considered as the main measure of value and creating the effects of procyclical value of capital in the conditions of technological shifts and crises.